Physical Characteristics and Ventilation Pattern in Uthai Thani city - Charoentrakulpeeti, Wapen (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The capability of urban ventilation is a major element of Urban Heat Island (UHI) intensity. The UHI intensity has an impact on human thermal comfort and varies in the each city. The well planned and designed cities with a consideration in urban ventilation get low heat accumulation. Thus, this study aims to identify physical characteristics and ventilation patterns of Uthai Thani municipality. The results show that Uthai Thani areas generally are residential and agricultural land uses, vegetation land cover and open space geometry. The impact of these physical characteristics on temperature between in the city and the suburb is not significant difference. The ventilation of the city has blown from southwest, northeast and south to north. Although, the influence of physical characteristics of Uthai Thani city on UHI intensity is low, it still need to take a consideration in land cover, land use, and ratio of building height and street width cooperating with the ventilation for the future urban expansion by (1) preserving vegetation and water land cover, (2) keeping agricultural land use in east and south of the city and allowing urban expansion in north areas, (3) considering the designation of building height, building gap and building width including the transportation routes parallel with the wind direction (north-south) in order to enhance fine urban ventilation.